1996
DOI: 10.1126/science.272.5258.97
|View full text |Cite
|
Sign up to set email alerts
|

The Energetics of Hydrogen Bonds in Model Systems: Implications for Enzymatic Catalysis

Abstract: Low-barrier or short, strong hydrogen bonds have been proposed to contribute 10 to 20 kilocalories per mole to transition-state stabilization in enzymatic catalysis. The proposal invokes a large increase in hydrogen bond energy when the pKa values of the donor and acceptor (where Ka is the acid constant) become matched in the transition state (delta pKa=0). This hypothesis was tested by investigating the energetics of hydrogen bonds as a function of delta pKa for homologous series of compounds under nonaqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
244
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(260 citation statements)
references
References 60 publications
14
244
1
1
Order By: Relevance
“…The increased stabilization is most likely to be the result of the combined contributions from two known effects on hydrogen bonds exposed to the bulk solvent: (i) Becker et al (61) have elegantly demonstrated that the interior of both DNA and RNA duplexes are devoid of water by showing a significant decrease in acridinium ester hydrolysis inside a complementary double helix compared to mismatched duplexes. Further, Shan et al have shown that the strength of hydrogen bonding is proportional to the dielectric of the solvent (62,63). Enzymatic catalysis is proposed to be achieved as the interior of the enzyme has a much lower dielectric than the surrounding solvent, making the hydrogen bonds stabilizing the transition state stronger inside the active site than free in solution, thereby catalyzing the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The increased stabilization is most likely to be the result of the combined contributions from two known effects on hydrogen bonds exposed to the bulk solvent: (i) Becker et al (61) have elegantly demonstrated that the interior of both DNA and RNA duplexes are devoid of water by showing a significant decrease in acridinium ester hydrolysis inside a complementary double helix compared to mismatched duplexes. Further, Shan et al have shown that the strength of hydrogen bonding is proportional to the dielectric of the solvent (62,63). Enzymatic catalysis is proposed to be achieved as the interior of the enzyme has a much lower dielectric than the surrounding solvent, making the hydrogen bonds stabilizing the transition state stronger inside the active site than free in solution, thereby catalyzing the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies and debates have appeared in the literature since the idea of low barrier hydrogen bond (LBHB or SSHB) was first proposed (12)(13)(14)(15). Two of the key questions are the strength of the LBHB and its contribution to the rate enhancement of the reaction catalyzed by the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…A second one is the increase of hydrogen bond strength induced by decreasing the dielectric constant and concomitant formation of transient charges (16). It appears that this aspect of MCADH is an example for what was suggested recently by Shan and Herschlag (13,55). A third concept is the combined effect of H-bonds, dielectric changes, and charge rearrangements on the redox potentials of substrate and flavin (i.e., the redox partners, 43).…”
Section: Discussionmentioning
confidence: 99%
“…A crucial issue in the dehydrogenation reaction of acylCoA dehydrogenase is the mode and extent of activation of RC-H. For efficient catalysis, current concepts assume that the microscopic pK a values of two partners involved in the transfer of one H + between them have similar values (12,13). The microscopic pK a of Glu376sCOO -recently has been determined to be ≈6 in uncomplexed enzyme (14).…”
mentioning
confidence: 99%